Evaluasi Kinerja Algoritma Penjadwalan Weighted Round Robin Pada Wimax - Sukiswo, Sukiswo (Transmisi, 2008)
This paper simulate WiMAX network with the implementation of Weighted Round Robin (WRR) based scheduler. This WiMAX simulation is made in five scenario, where each of scenario has varied number of Subscriber Station (SS) using particular class of service. Classes of services used in this simulation are Unsolicited Grant Service (UGS), real time Polling Service (rtPS), extended real time Polling Service (ertPS), non real time Polling Service (nrtPS), dan Best Effort (BE). The design of WiMAX network simulation use Network Simulator  – 2 (NS-2) version 2.29.3. While, WiMAX module that installed to NS-2 is developed by Network & Distributed System laboratory (NDSL),with 2.03 version. This Final Project is aimed at evaluating WRR based scheduler in relation to WiMAX network performance. Performance metrics reported in this work are throughput, packet loss, and average delay. The result of test shows that WRR based scheduler has good performance to suppress packet loss, which the value of packet loss decrease until 0 %. WRR give high throughput for class of service that has high value of Minimum Reserved Traffic Rate (MRTR) and priority. The average delay that obtained has very small value in mikro second. It shows that WRR has good performance to suppress average delay. Level of throughput and average delay in every service class is affected by the number of SS using that particular service class.Keywords – WiMAX, NS-2, Weighted Round Robin